Overexpression of a Novel Arabidopsis Gene SUPA Leads to Various Morphological and Abiotic Stress Tolerance Alternations in Arabidopsis and Poplar - Cai, Changyang; Wang, Wenjia; Ye, Shanwen; Zhang, Zhiliang; Ding, Wensha; Xiang, Mengqi; Wu, Chu; Zhu, Qiang (Frontiers in Plant Science, 2020)
With the development of sequencing technology, the availability of genome data is rapidly increasing, while functional annotation of genes largely lags behind. In Arabidopsis, the functions of nearly half of the proteins are unknown and this remains one of the main challenges in current biological research. In an attempt to identify novel and rapid abiotic stress responsive genes, a number of salt-up (SUP) regulated genes were isolated by analyzing the public transcriptomic data, and one of them, SUPA, was characterized in this study. The expression of SUPA transcripts was rapidly up-regulated by various abiotic stress factors (<15 min), and SUPA protein is mainly localized in the peroxisome. Overexpression of SUPA in Arabidopsis leads to the elevated accumulation of reactive oxygen species (ROS), strong morphological changes and alternations in abiotic stress tolerance. The transcriptome analysis showed changes in expression of genes involved in stress response and plant development. Interestingly, ectopic overexpression of SUPA in poplar leads to a dwarf phenotype with severely curved leaves and changes in the plant tolerance of abiotic stresses. Our study reinforces the potential roles of SUPA in normal plant growth and the abiotic stress response.